Bazaar aesthetics: On excess and economic rationality. (May 2021) - Deka, Maitrayee
For more than a century, social theoretical writings on consumer culture and commodity aesthetics have concentrated on the world of capitalist commodities and commercial spaces: on brands, shopping malls and global media culture. Popular commodity aesthetics have had a marginal presence in the literature. However, today, as the popular masses are entering commercial culture to an unprecedented extent, through cheap electronics, ubiquitous internet connectivity and accessible knock-offs, popular commodity aesthetics have increased in importance. In this article, I use fieldwork in Delhi's electronics bazaars to develop an inside perspective on the popular aesthetic of the bazaar. I argue that bazaars are characterized by excess: the excess of a seemingly chaotic architecture, household objects, and unhindered sociality. The excess is not simply a symptom of an underlying irrationality. It is deeply embedded in the social and economic life of bazaars and contributes towards the ability of small-scale commerce to endure and survive.